Margy Gerber, et al.: Studies in GDR Culture and Society 6: Selected Papers from the Eleventh New Hampshire Symposium on the German Democratic Republic - Herbert A Arnold (GDR Bulletin, 1987)
Lanham: University Press of America, 1986. viii + 206 p.